Understanding Followers Feedback in TikTok Videos: A Netnographic Analysis on English Learning Content - Mayaputri, Velmi; Wahyuningsih (Buletin Edukasi Indonesia, 2025)
The growth of social media advances breaking the limited access of English learning experience. One of the massive users of social media currently is the TikTok application. This study examined followers’ feedback on the English learning content created by @kadang.sokinggris TikTok account. The English learning content presented by this account consists of vocabulary mastery, pronunciation, English version, and word differences. His teaching method is "scolding his followers.". This study utilized the Netnography approach to explore online behaviour and interaction in the comment box of 30 videos. The videos consist of 7 vocabulary mastery contents, 8 pronunciation contents, 7 English version contents, and 8 word differences contents. It was found that majority of the video comments were positive. The videos in vocabulary mastery content presented contextual examples to help the followers understand how to use vocabulary in a proper context. In addition, it was discovered that there are oral and written feedback and interaction between the content creator and the followers. As presented in pronunciation contents, the content creator challenged the followers to read the four words, and afterward, he corrected how to read by “scolding” his followers that what was said was wrong in pronunciation. In the comment section, many followers still get the mispronounced words. Key findings were that @kadang.sokinggris TikTok account provides English learning content with unique features, clarity of voice in delivering material, and techniques presented that are different from those of other content creators. So, it can be claimed that the Tiktok application becomes an online version of English learning media in today’s digital era.